Pelatihan Pelaporan Perpajakan PPH21 Pada Siswa Siswi SMK Tangerang - Benyamen Minggus Melatnebar; Yopie Chandra; Trida Trida; Peng Wi; Yunia Oktari (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Education is a means to improve and develop students’ knowledge and skills to face competition in the industrial word. One of the problems faced by vocational school graduates is the low understanding of taxation among vocational school graduates. School principals, department heads and teachers have done many things to improve the competency of their graduate students, starting from improving the curriculum, procuring learning books, improving facilities and infrastructure, as well as training for students. Tax training regarding personal income tax, provided by Buddhi Dharma University lecturers and students, is an effort to improve the competency of vocational school student gradates. This traning is carried out with the hope that vocational school student graduates will have good soft skills and can apply or implement the results of tihis tax in the word of work.